Learners’ Attitudes Toward English Pronunciation and Their Ability to Distinguish Phonetic Features and Pronounce Vocabulary Before and After Completing a Course in English Articulatory Phonetics - Sasanapradit, Walaiporn (Journal of Buddhist Education and Research (JBER), 2025)
This quasi-experimental study aimed to examine the relationship between students’ attitudes toward English pronunciation and their abilities to identify phonetic features and pronounce vocabulary before and after completing a course in English articulatory phonetics. The participants, selected through purposive sampling, consisted of 32 undergraduate English majors. Research instruments included (1) an attitude assessment questionnaire, (2) four phonetic discrimination tests, and (3) a set of vocabulary items. Data were analyzed using descriptive statistics, including percentage, median, and mode. The findings revealed that students' attitudes toward English pronunciation improved significantly in a positive direction after completing the course. This change positively correlated with their enhanced phonetic discrimination abilities as assessed through listening and dictation activities, with post-test scores reaching very high levels—96.9%, 91.6%, 96.4%, and 90.6%, respectively. Pre-test scores ranged from low to moderate levels—67.5%, 43.4%, 58.9%, and 37.5%, respectively. Similarly, students’ pronunciation proficiency improved markedly. In pronunciation tasks involving the use of an English-English dictionary, students achieved the highest quality of performance, with a median score of 4.7 and a mode of 5. Prior to the course, their performance in pronunciation tasks using a Thai-English dictionary was at a moderately low level, with a median of 2.8 and a mode of 3. These findings demonstrate that ‘attitude’ plays a crucial role in students’ academic success alongside intellectual ability. A positive attitude toward English pronunciation significantly supports the improvement of students' abilities to identify phonetic features and pronounce English vocabulary.